Pemodelan 2 dimensi data magnetotellurik berdasarkan analisis phase tensor dalam penentuan geoelectrical strike dan dimensionalitas data di Lapangan Panas Bumi “X” - Fitra Ramdhani; Agus Setyawan; Imam B. Raharjo; Lendriadi A. (Youngster Physics Journal, 2017)
Magnetotelluric research has been done on the geothermal field "X" aims to indentify dimensionality of data, direction of geoelectrical strike and map resistivity distribution of subsurface structure. Before modelling 2 dimensional subsurface structure, MT data must go through stage quality control data, analysis of dimensionalitas data and analysis direction of geoelectrical strike to get 2 dimensional structure model of the subsurface are accurate. The stages of quality control data was done by eliminate the points in the curve of resistivity and phase which out of the trend that is considered as noise. Dimensionality data analysis use curve of three parameters invariant phase tensor i.e phi maximum, phi minimum and beta. Analysis of  the geolectrical strike direction was done by showing a reduction of angle  and  in rose diagram. Overall the analysis phase tensor was performed on 60 tensor magnetotelluric data in the geothermal field "X". Modeling subsurface resistivity structure use the scheme forward modelling and inverse modelling. The results of selection cross power showed that magnetotelluric data are dominated by good quality data. The results of dimensionality data analysis indicates that the dimensionality data of MT data in the geothermal field "X" consists of structure with dimensionality 1D, 2D and 3D structure. Structure with dimensionality 1D is in  frequency range 320 – 44 Hz, Structure with dimensionality 2D is in frequency range 44 – 0,3 Hz and structure with dimensionality 3D is in  frequency range 0.3 – 0.004 Hz in the geothermal field "X". Rose diagram in frequency range 320 – 0.3 Hz was combined with direction of regional structure in geothermal field "X" indicates that the direction of geoelectrical strike is N330oE. 2 dimensional modeling has been done in the frequency range 320 – 0,3 Hz. Data is rotated in the direction of geoelectrical strike before the modeling stage. 2 dimensional model consisting of five line perpendicular to the direction of the structure in the field. 2 dimensional model  show caprock layer has s resistivity range 5-20 Ohm-m that thicken to the Northwest while the reservoir layer has a resistivity range 80-120 Ohm-m are thinned to the Northwest. The heat source has a resistivity range 400-500 Ohm-m and located at depth  3.5 km below the surface.Keywords: Dimensionality, geoelectrical strike, distortion, model 2 dimensi